Methods of Partial Discharge Localization in High Voltage Transformers - Rahimbakhsh, Mahdi (TEWISS – Technik und Wissen GmbH, 2021)
In this thesis, three PD localization methods are developed and discussed. The first method is based on calculated sectional transfer function of the winding in power transformers with design information. This method is based on the multi-conductor transmission line theory which improves the accuracy of PD localization using the design information of the transformer. And further software provided for PD localization is presented. The second method, a highly functional and simplified method is discussed. This method allows investigating and suggesting the possibility of detection of failures of PD with the least amount of time and information regarding the interior design of power transformer. The third method utilizes a machine learning algorithm by simplification of the measurements. The proposed method uses measured partial discharge signals with high frequency current transformer (HFCT) and processed them using a curve fitting (CF) method with a high rated fitting quality. The extracted coefficients of the selected function terms are then evaluated in order to find the PD location.